Single-Cell RNA Sequencing Reveals Tissue Compartment-Specific Plasticity of Mycosis Fungoides Tumor Cells - Rindler, Katharina; Bauer, Wolfgang M.; Jonak, Constanze; Wielscher, Matthias; Shaw, Lisa E.; Rojahn, Thomas B.; Thaler, Felix M.; Porkert, Stefanie; Simonitsch-Klupp, Ingrid; Weninger, Wolfgang; Mayerhoefer, Marius E.; Farlik, Matthias; et al. (Frontiers in Immunology, 2021)
Mycosis fungoides (MF) is the most common primary cutaneous T-cell lymphoma. While initially restricted to the skin, malignant cells can appear in blood, bone marrow and secondary lymphoid organs in later disease stages. However, only little is known about phenotypic and functional properties of malignant T cells in relationship to tissue environments over the course of disease progression. We thus profiled the tumor micromilieu in skin, blood and lymph node in a patient with advanced MF using single-cell RNA sequencing combined with V-D-J T-cell receptor sequencing. In skin, we identified clonally expanded T-cells with characteristic features of tissue-resident memory T-cells (TRM, CD69+CD27-NR4A1+RGS1+AHR+). In blood and lymph node, the malignant clones displayed a transcriptional program reminiscent of a more central memory-like phenotype (KLF2+TCF7+S1PR1+SELL+CCR7+), while retaining tissue-homing receptors (CLA, CCR10). The skin tumor microenvironment contained potentially tumor-permissive myeloid cells producing regulatory (IDO1) and Th2-associated mediators (CCL13, CCL17, CCL22). Given their expression of PVR, TNFRSF14 and CD80/CD86, they might be under direct control by TIGIT+CTLA4+CSF2+TNFSF14+ tumor cells. In sum, this study highlights the adaptive phenotypic and functional plasticity of MF tumor cell clones. Thus, the TRM-like phenotype enables long-term skin residence of MF cells. Their switch to a TCM-like phenotype with persistent skin homing molecule expression in the circulation might explain the multi-focal nature of MF.